Comparison of Clinical Characteristics and Mortality Outcome in Critical COVID-19 Patients Infected with Alpha and Omicron Variants - Cheng HI; Chang KW; Wu BC; Teo MY; Hung WS; Wu HM; Huang ACC; Lin CW; Lin TY; Lin HC; Chiu CH; Lin SM (Infection and Drug Resistance)
Hsin-I Cheng,1 Ko-Wei Chang,1 Bing-Chen Wu,1 Mei-Yuan Teo,1 Wei-Syun Hung,1 Hao-Ming Wu,1 Allen Chung-Cheng Huang,1 Chang-Wei Lin,2 Ting-Yu Lin,1 Horng-Chyuan Lin,1 Cheng-Hsun Chiu,3,4 Shu-Min Lin1,5– 7 1Department of Thoracic Medicine, Chang Gung Memorial Hospital, Linkuo, Taiwan; 2Department of Thoracic Medicine, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 3Department of Pediatrics, Chang Gung Children’s Hospital, Chang Gung University College of Medicine, Taoyuan City, Taiwan; 4Molecular Infectious Disease Research Center, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 5Department of Respiratory Therapy, Chang Gung Memorial Hospital, Linkuo, Taiwan; 6School of Medicine, National Tsing Hua University, Hsin-Chu, Taiwan; 7School of Medicine, Chang Gung University, Taoyuan, TaiwanCorrespondence: Shu-Min Lin, Department of Thoracic Medicine, Chang Gung Memorial Hospital, 199 Tun-Hwa N. Road, Taipei, Taiwan, Tel + (886) 3-328 1200 ext. 8467, Email smlin100@gmail.comObjective: Early reports have indicated that the Omicron variant of coronavirus disease 2019 (COVID-19) may be associated with low mortality. However, the mortality rate of critical patients in Taiwan with COVID-19 caused by different variants has not been well described.Methods: This retrospective cohort study was conducted at the Linkou Branch of Chang Gung Memorial Hospital, Taiwan, from April 2020 to September 2022. Critically ill patients who had confirmed SARS-CoV-2 infection and were on mechanical ventilation (MV) were enrolled. Demographic data, laboratory results, and treatment information were collected and analyzed. In addition, clinical outcomes for different SARS-CoV-2 variants were analyzed.Results: This study included 110 critical patients with COVID-19 who required intubation and intensive care unit (ICU) admission. Among these patients, 46 (41.8%) required intensive care during Alpha predominance period and 64 (58.2%) during the Omicron predominance period. The Alpha group had a higher body mass index, had a longer ICU stay, and included more patients with acute respiratory distress syndrome, and the Omicron group included more active smokers, had more comorbidities, had worse initial laboratory data (including higher white blood cell counts, prothrombin time [PT], activated partial prothrombin time, blood urine nitrogen levels, and creatine levels), and had higher in-hospital mortality rates (40.6% vs 15.2%, p = 0.004). The independent risk factors for in-hospital mortality, were Charlson Comorbidity Index (CCI) ≥ 3 and higher PT and creatine levels.Conclusion: Our study discovered that CCI ≥ 3, elevated serum creatine levels, and prolonged PT were independently associated with a high mortality rate in patients with critical COVID-19. Patients with those risk factors may require intensive monitoring during their treatment course.Keywords: COVID-19, intensive care, CCI, Charlson Comorbidity Index, mortality